Fertilization in the production of Agave angustifolia Haw in the nursery of Sola de Vega, Oaxaca - Velasco-Velasco, Lidia; Corlay-Chee, Langen; Camacho-Montoya, Jesús Alberto; Sánchez-de Jesús, Marco Antonio; Fuentes-Franco, Héctor Hugo; Valle-Guadarrama, Salvador (Ecosistemas y Recursos Agropecuarios, 2025)
Mezcal production in Villa Sola de Vega is a key component of the local economy, which has led to an increase in its production and demand for raw materials. In response, large areas of mezcal cultivation have been established, nursery production for transplanting into the field has intensified, and strategies aimed at reducing production times have been sought. However, this massive production of plants is associated with the irrational use of agrochemicals, which causes a progressive deterioration in soil quality and fertility. Therefore, the objective of this study was to evaluate the application of guano to the growth of Agave angustifolia as a sustainable alternative for plant production and soil fertility improvement. Four treatments were evaluated: a control, six kilograms of guano, conventional fertilization, and a combination. The experimental design was completely randomized. The evaluation was conducted 208 days after transplantation, measuring growth variables, total soluble solids concentration in sap, mycorrhizal colonization, nitrogen-fixing bacteria, and parameters related to soil fertility. Guano application improved soil fertility parameters and favored the soil microbiome, as evidenced by the increased plant height, smaller rosette diameter, and biomass. It is concluded that guano, a local resource of low economic value, is a sustainable alternative for improving soil fertility and Agave angustifolia production.